Les espaces numériques scolaires et l’accès du grand public à l’information numérique au Sénégal - Maty Diallo-Dia; Ansoumana Sane (Netcom)
This article is the result of a study on digital learning spaces in the Dakar area. Our methodology followed three complementary steps: a quantitative survey, a qualitative survey, and a review of current literature on the subject. From kindergarden to college, the number of digital learning spaces (with multimedia tools and internet access) is growing so fast that one might wonder about the scenarios and logic that led to their establishment and the competences of the actors behind it. The results show the existence of several categories of learning spaces based on their organization or the objectives that led to their creation. They also show how digital learning spaces help reduce the digital divide in Senegal and, in addition to the classical use of ICT, come in handy in personal projects as well, and how they contribute to the development of the areas in which they are established…